Psychological Well-Being of Juvenile Prisoners in Bandung - Rohman Hikmat; Iyus Yosep; Popy Siti Aisyah; Shella Febrita Puteri Utomo (Fakultas Kedokteran Universitas Sriwijaya, 2024)
The psychological well-being of juvenile prisoners is very important in supporting their rehabilitation process, but is often neglected due to internal and external factors that affect their psychological condition. The correctional environment which is full of social stigma, limited psychological support, and mental conditions before detention are major challenges for juvenile prisoners. This study aims to determine the description of psychological well-being in juvenile prisoners in Bandung. This study used a quantitative descriptive research design with a total sampling technique. The research sample consisted of 80 juvenile prisoners in correctional institutions. Data collection was carried out using the Psychological Well-Being Scale questionnaire consisting of 42 question items with a Likert scale. Data analysis was carried out using a frequency distribution test to describe the level of psychological well-being based on high, medium, and low categories. The results showed that 62.5% of juvenile prisoners had moderate psychological well-being, 27.5% were in the low category, and only 10% had high psychological well-being. Factors such as mental conditions before detention, social interactions, and the physical environment in correctional institutions affect their level of psychological well-being. Social stigma and lack of psychological support are major challenges in improving their psychological well-being. Support from psychiatric nurses in correctional institutions plays an important role in helping juvenile inmates cope with stress and adapt to the detention environment. This study emphasizes the importance of psychological interventions to improve their well-being, especially by improving social support and reducing social stigma.